Misunderstanding Flight Part 1: A Century of Flight and Lift Education Literature - Graham Wild (MDPI AG, 2023)
The science education literature is littered with "new", "correct", "novel", "explanations", "theories", and "approaches" to aerodynamic lift. One might infer from reading the growing number of these articles that there is a fundamental gap in classical physics, where our scientific prowess has failed us. In fact, if you read popular sources, you would believe "no one can explain why planes stay in the air". This is a disconcerting thought to have while sitting inside a modern engineering marvel provided by Boeing or Airbus. However, rationally, since you are sat in that fuel-efficient and safe aeronautical wonder, the logical conclusion is that some are obviously aware of why planes stay in the air. In this paper, a century of educational literature on the topic of aerodynamic lift and flight is presented. The body of literature encompasses 140 articles, commencing in 1920. It is obvious from the content contained within them that there is more of a misunderstanding rather than an understanding of flight in the education context. There are two paradigms treated as mutually exclusive: those using Bernoulli and those using Newton. Throughout the literature, there are gems lost in the rubble; if the reader does not have an understanding, how will they know what is worth reading? This review attempts to clarify what is worth reading, by presenting a qualitative overview of aerodynamics education in undergraduate engineering, to understand why these opposing camps exist in the literature.